PELAKSANAAN REHABILITAS JALAN KOMPLEK PANGKALAN TNI TNI AU LANUD SRI MULYONO HERLAMBANG PALEMBANG - Abdul Aziz, Mohamad; Firdaus, Firdaus (Ensiklopedia of Journal, 2024)
Roads are land transportation infrastructure which includes all parts of the road, including complementary buildings and equipment intended for traffic, which are on the ground surface, above the ground surface, below the ground and water surface, and above the water surface. except railways, truck roads and cable roads. The function of highways as transportation infrastructure in economic activities is to equalize the economy with the highway as a link. Rehabilitation is the answer to the damage that occurs due to excessive vehicle loads and frequently changing weather and climate. Rehabilitation of road works is the resurfacing, restoration and rehabilitation of existing pavement surfaces to extend the useful life, improve the performance and durability of the pavement structure. To restore the service condition of this road, road maintenance is needed. One type of road maintenance is road improvement. Road improvements can take the form of improving the road pavement structure and also widening the road to increase road capacity. The government builds infrastructure in the field of land transportation according to the level of needs of each region, in order to realize the development of a region. Development of this means of transportation. This research is a research study in the field which aims to find out whether the method of carrying out road rehabilitation work on the air base road rehabilitation project at the Sri Mulyono TNI Au complex, South Sumatra, is in accordance with the general specifications for Bina Marga 2023.Keywords: implementation of road rehabilitation.